(untitled) (Annals of Medical Research, 2024)
Aim: Cancer stands as a significant health issue in our era, with lung cancer being among the most widespread types in both Turkey and worldwide. The diagnosis may be delayed due to the late detection of symptoms and signs. Cancer stem cells cause the initiation and progression of cancer. There is a risk of cancer recurrence due to cancer stem cells that cannot be destroyed. Therefore, it is important to detect cancer stem cells and prevent the proliferation of these stem cells. Materials and Methods: In the Pathology Department of Pamukkale University Faculty of Medicine, 72 squamous cell carcinoma and 51 adenocarcinoma cases diagnosed with non-small cell lung cancer were retrospectively examined. Nucleostemin and CD133 expression levels were evaluated immunohistochemically in sections taken from cancerous tissue samples of the cases. Results: Disease-free survival and tumor stages of the cases and immunohistochemical expression level were compared. Nucleostemin and CD133 expression was commonly observed in tumor tissue from both adenocarcinoma and squamous cell carcinoma cases. Conclusion: Therefore, in line with the data we obtained, we think that both nucleostemin and CD133 cannot be used as prognostic markers in non-small cell lung cancer.